Non‐clinical safety and biodistribution of AS03‐adjuvanted inactivated pandemic influenza vaccines. Issue 12 (27th February 2015) - Segal, Lawrence; Wouters, Sandrine; Morelle, Danielle; Gautier, Gaëlle; Le Gal, Julien; Martin, Thomas; Kuper, Frieke; Destexhe, Eric; Didierlaurent, Arnaud M.; Garçon, Nathalie
Abstract Pandemic‐influenza vaccines containing split‐inactivated‐virus antigen have been formulated with the immunostimulatory Adjuvant System AS03 to enhance the antigen immunogenicity and reduce antigen content per dose. AS03 is an oil‐in‐water emulsion containing α‐tocopherol, squalene and polysorbate 80. To support the clinical development of AS03‐adjuvanted pandemic‐influenza vaccines, the local and systemic toxicity of test articles containing split‐influenza A(H5N1) and/or AS03 were evaluated after 3–4 intramuscular (i.m.) injections in rabbits. Treatment‐related effects were restricted to mild inflammatory responses and were induced primarily by the test articles containing AS03. The injection‐site inflammation was mild at 3 days, and minimal at 4 weeks after the last injection; and was reflected by signs of activation in the draining lymph nodes and by systemic effects in the blood including a transient increase of neutrophils. In addition, a study in mice explored the biodistribution of A(H5N1) vaccines or AS03 through radiolabelling the antigen or constituents of AS03 prior to injection. In this evaluation, 57–73% of AS03's principal constituents had cleared from the injection site 3 days after injection, and their different clearance kinetics were suggestive of AS03's dissociation. All these AS03 constituents entered into the draining lymph nodes within 30 min after injection. In conclusion, the administration of repeated doses of the H5N1/AS03 vaccine was well tolerated in the rabbit, and was primarily associated with transient mild inflammation at the injection site and draining lymph nodes. The biodistribution kinetics of AS03 constituents in the mouse were consistent with AS03 inducing this pattern of inflammation. Copyright © 2015 John Wiley & Sons, Ltd.